Handbook of Heterogeneous Catalysis 2008
DOI: 10.1002/9783527610044.hetcat0157
|View full text |Cite
|
Sign up to set email alerts
|

Aromatization of Light Alkanes

Abstract: The sections in this article are Introduction Thermodynamics of Alkane Aromatization Catalysts Ga / HZSM ‐5 Pt / KL Other Catalysts for Alkane Aromatization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Increasing shale gas production in the United States has incentivized the conversion of light alkanes derived from shale gas to alkenes and aromatics, primarily benzene, toluene, and xylenes (BTX). BTX are traditionally produced via catalytic reforming of naphtha and are important feedstocks for the production of plastics, fibers, resins, and films. Prior work has shown that dehydroaromatization involves initial alkane dehydrogenation to form alkenes, which then undergo oligomerization, cyclization, and further dehydrogenation to form the final aromatic products. Lewis acidic metal cations exchanged into zeolites are used industrially to catalyze the dehydrogenation and subsequent aromatization of light alkanes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing shale gas production in the United States has incentivized the conversion of light alkanes derived from shale gas to alkenes and aromatics, primarily benzene, toluene, and xylenes (BTX). BTX are traditionally produced via catalytic reforming of naphtha and are important feedstocks for the production of plastics, fibers, resins, and films. Prior work has shown that dehydroaromatization involves initial alkane dehydrogenation to form alkenes, which then undergo oligomerization, cyclization, and further dehydrogenation to form the final aromatic products. Lewis acidic metal cations exchanged into zeolites are used industrially to catalyze the dehydrogenation and subsequent aromatization of light alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis acidic metal cations exchanged into zeolites are used industrially to catalyze the dehydrogenation and subsequent aromatization of light alkanes. In particular, BP/UOP’s Cyclar process utilizes Ga/H-MFI zeolites for the dehydroaromatization of C 3 –C 4 alkanes. While Ga/H-MFI has been explored extensively for this purpose, the Ga hydride species contained in this catalyst ([GaH] 2+ and [Ga­(H) 2 ] + cations) are active for alkane cracking as well as dehydrogenation. For this reason, and because Ga is a relatively expensive element, efforts have been undertaken to find a more earth-abundant element and one that would exhibit low selectivity to alkane cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Ethane and propane present in the condensable part of shale gas are important feedstocks for the production of aromatics, namely, benzene, toluene, and xylenes, which serve as raw materials for the production of plastics and pharmaceuticals. Industrial processes, such as Aromax (Chevron), Aroforming (IFP/Salutec), Cyclar (BP/UOP), and Z-Forming (Mitsubishi Oil and Chiyoda), typically utilize zeolite catalysts for alkane dehydroaromatization . In particular, gallium-exchanged H-MFI zeolites (Ga/H-MFI), employed in the Cyclar process, are active and selective for light alkane dehydroaromatization.…”
Section: Introductionmentioning
confidence: 99%
“…1−4 Industrial processes, such as Aromax (Chevron), Aroforming (IFP/Salutec), Cyclar (BP/UOP), and Z-Forming (Mitsubishi Oil and Chiyoda), typically utilize zeolite catalysts for alkane dehydroaromatization. 3 In particular, galliumexchanged H-MFI zeolites (Ga/H-MFI), employed in the Cyclar process, 3 are active and selective for light alkane dehydroaromatization.…”
Section: Introductionmentioning
confidence: 99%